Innovation In Teaching Islamic Inheritance Material With Canva At The Indonesian Aviation Polytechnic In Curug - Abdusshomad, Alwazir (Sekolah Tinggi Agama Islam Darul Qur'an Payakumbuh, 2025)
The teaching of Islamic Religious Education (IRE) in the digital era necessitates continuous innovation to enhance student engagement and comprehension, particularly in complex topics such as Islamic inheritance law. This study aims to develop and evaluate the validity of an interactive learning medium based on Canva, specifically designed for inheritance materials at the Indonesian Aviation Polytechnic Curug. Employing a Research and Development (R&D) approach, this study adapts the 4-D model (Define, Design, Develop) proposed by Thiagarajan, Semmel, and Semmel (1974). The research was conducted within the D-III Airport Operation Program (OBU), Class 18 C. The findings reveal that Canva-based media has significant potential to address students' low learning motivation. Through expert validation involving a technology lecturer (media expert) and an Islamic education lecturer (content expert) using a Likert-scale questionnaire, the interactive Canva learning tool demonstrated an exceptionally high level of validity, achieving a 98% validation score for both media and content aspects. These results confirm the appropriateness of the visual design, ease of navigation, and the relevance and depth of the instructional content. The outcomes of this research are expected to provide valuable insights for educators and researchers regarding the effective integration of Canva technology to enhance the quality of IRE learning, particularly in the teaching of Islamic inheritance law.